American Historical Explanations : A Strategy for Grounded Inquiry - Wise, Gene (Book collections on Project MUSE., 1980)
In this new edition of American Historical Explanations,Gene Wise expands his examination of historical thinking to include the latest work in American Studies, the new social history, ethnography, and psychohistory. Wise asserts that historians address their subjects through an intervening set of assumptions, or what he calls ""explanation forms,"" similar to the philosophical paradigms that Thomas Kuhn has found in scientific inquiry. Through analysis of historical-cultural texts (including the work of V. L. Parrington, Lionel Trilling, and Perry Miller) he defines the forms used by several.